2002
DOI: 10.1248/bpb.25.149
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Transit and Drug Absorption

Abstract: Oral drug administration is the most convenient and common for drug therapy and it is, therefore, very important and useful to estimate the absorbability of drugs and to predict the plasma concentration profile of drugs after oral administration for the development of novel drugs and/or novel dosage form and the designation of the dosage regimen. Generally, the absorbability of drugs has been estimated by in-situ recirculation studies, in-situ closed loop studies or the analysis by the simple compartment model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
114
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(122 citation statements)
references
References 54 publications
(88 reference statements)
3
114
2
Order By: Relevance
“…In the present work, a physiologically relevant simulation tool was developed to model the absorption, biotransformation, metabolism, and clearance of 5-ASA. In the model presented, passive absorption, saturable absorption, biotransformation, and transit kinetics were simultaneously considered, whereas general purpose absorption and transit models (Ito et al, 1999;Agoram et al, 2001;Kimura and Higaki, 2002) exclude extracellular metabolism and exsorption (efflux transport). On the other hand, not unlike our model, the traditional and segregated-flow models developed by Cong et al (2000) comprehensively illustrate the interactions among the effective flow to the intestine, absorption rate, and intestinal epithelial cell activities including enzymatic, secretory, and metabolism activities.…”
Section: Discussionmentioning
confidence: 99%
“…In the present work, a physiologically relevant simulation tool was developed to model the absorption, biotransformation, metabolism, and clearance of 5-ASA. In the model presented, passive absorption, saturable absorption, biotransformation, and transit kinetics were simultaneously considered, whereas general purpose absorption and transit models (Ito et al, 1999;Agoram et al, 2001;Kimura and Higaki, 2002) exclude extracellular metabolism and exsorption (efflux transport). On the other hand, not unlike our model, the traditional and segregated-flow models developed by Cong et al (2000) comprehensively illustrate the interactions among the effective flow to the intestine, absorption rate, and intestinal epithelial cell activities including enzymatic, secretory, and metabolism activities.…”
Section: Discussionmentioning
confidence: 99%
“…Chiou et al quantitatively studied the impact of the unstirred water layer adjacent to the intestinal membrane on the rate and extent of absorption of passively absorbed drugs with different membrane absorption half-lives (10 -300 min) in humans (Chiou 1994). Results of this analysis suggested that the presence of the unstirred water layer is generally expected to have a relatively mild or insignificant effect on the rate of absorption and an insignificant effect on the extent of absorption (Kimura and Higaki 2002).…”
Section: Unstirred Water Layermentioning
confidence: 99%
“…The absorption rate of a drug molecule is generally a function of drug absorption through the GIT, which is determined by the residence time and absorption in each GIT segment (Kimura and Higaki 2002). In general, gastric transit time impacts the systemic exposure of rapidly dissolved and well absorbed drugs.…”
Section: Gastrointestinal Transit Timesmentioning
confidence: 99%
See 1 more Smart Citation
“…The quality and predictive power of new models will be judged in comparison with experimental data as well as in comparison with other models (as an example see, e.g., the study in [14]). A variety of different models for oral absorption are avaliable [15][16][17][18][19]. By comparing these absorption models for different test compounds, it would be possible to understand the "domain of applicability" of each model, i.e., under which conditions and for which class of compounds the models give the most reliable predictions.…”
Section: In Silico Modelingmentioning
confidence: 99%